Lotus and Pharmakon: Drugs in the Dialectic of Enlightenment - Shmugliakov, Pioter (Eidos. A Journal for Philosophy of Culture, 2025)
This essay explicates the position of Adorno and Horkheimer’s Dialectic of Enlightenment on the problem of drugs. At the focus of my analysis are the passages in “Excursus I: Odysseus or Myth and Enlightenment” which interpret the Homeric myth of the Lotus-eaters in terms of the modern phenomenon of substance abuse. Since the Dialectic reads the Odyssey as the fundamental history of subjectivity, the indictment of drugs the authors recognize in the myth acquires, as it were, a transhistorical status. Building upon the work of Jacques Derrida and applying his notion of the pharmakon as a metaphysical concept of the drug, I show that the Dialectic reveals a much more ambivalent picture. The backbone of my argument is a structural comparison between the book’s treatment of the Lotus and its interpretations of the myths of the Sirens and Circe, standing, on this account, for art and sex respectively.